The Association of Preoperative Malnutrition with Delayed Wound Healing and Related Postoperative Complications: A Systematic Review - Pretika Prameswari; Raka Jati Prasetya; Mutia Juliana (International Medical Journal Corp. Ltd, 2025)
Introduction: Preoperative malnutrition is a prevalent and modifiable risk factor in surgical patients, yet its full impact on postoperative recovery remains a critical area of clinical investigation. The objective of this systematic review is to comprehensively synthesize the existing evidence linking preoperative malnutrition to delayed wound healing and a broad spectrum of other adverse postoperative outcomes. Methods: A systematic search of the PubMed, EMBASE, and Cochrane Library databases was conducted to identify relevant observational studies and meta-analyses. Studies were selected if they investigated the association between a defined measure of preoperative malnutrition and postoperative outcomes in adult surgical patients. The methodological quality and risk of bias of included studies were rigorously assessed using the Cochrane